EMOTIONAL SCAFFOLDING: MENDING EMOTIONS IN SCIENCE EDUCATION - Carri, Remith George; Joseph, Asha (SCHOOL SCIENCE, 2021)
This paper is an effort to highlight the importance of emotional scaffolding in science learning which is emerging and contributory in effective science education. The role of emotions in improving learning engagement and interest in learning science is highlighted. Without undermining the importance of content knowledge, the added role of emotions to create an emotional attachment to the subject learnt is outlined. The authors used the concept of Pedagogical Content Knowledge and the concept of Zone of Proximal Development to stress and highlight the need for pedagogical knowledge of teachers as well as the support that a teacher should provide learners in their learning process. The significance of emotions in learning is highlighted and emotional scaffolding is proposed as a means to create interest and engagement among learners in science and science education.